2019
DOI: 10.2320/matertrans.mf201906
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modelling of High-Pressure Torsion: An Overview

Abstract: Finite element modelling (FEM) has been extensively performed to study the flow process, the distribution of hydrostatic stress and the temperature rise in materials processed by high-pressure torsion (HPT). This overview provides a summary and a critical assessment of the most important findings obtained by means of these FEM simulations which permitted a better understanding about the microstructural evolution during processing by HPT. For convenience, FEM investigations focused on examining the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 99 publications
0
19
0
2
Order By: Relevance
“…[13] One parameter that may produce recovery is the increase in temperature that occurs during the HPT process which has been well documented by finite element modeling. [16,43] The results from this modeling show that the temperature increases both due to the heat generated during the plastic deforming of the sample and due to the friction inherent in the material flow during the anvil rotation. Accordingly, it is important to investigate the influence of a temperature rise on the occurrence of recovery in the present study.…”
Section: Instantaneous Softening During Hpt Processingmentioning
confidence: 94%
“…[13] One parameter that may produce recovery is the increase in temperature that occurs during the HPT process which has been well documented by finite element modeling. [16,43] The results from this modeling show that the temperature increases both due to the heat generated during the plastic deforming of the sample and due to the friction inherent in the material flow during the anvil rotation. Accordingly, it is important to investigate the influence of a temperature rise on the occurrence of recovery in the present study.…”
Section: Instantaneous Softening During Hpt Processingmentioning
confidence: 94%
“…Several reports investigated the temperature rise due to heat generated during plastic deformation and friction inherent in the material flow during the anvil rotation through finite element modeling. [37][38][39] Recent investigations examined the temperature rise and corresponding microstructure changes in Al, Ag, and Cu during HPT processing and it was concluded that the temperature rise is of only minor significance in initiating dynamic recrystallization. [40,41] Accordingly, the recrystallization phenomenon in Al-0.1% Mg alloy appears to be mainly due to the formation of large fractions of lattice defects from the heavy shear strains.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature rise during HPT processing is a factor that may produce recovery and recrystallization in addition to the plastic strain applied on the material. Several reports investigated the temperature rise due to heat generated during plastic deformation and friction inherent in the material flow during the anvil rotation through finite element modeling . Recent investigations examined the temperature rise and corresponding microstructure changes in Al, Ag, and Cu during HPT processing and it was concluded that the temperature rise is of only minor significance in initiating dynamic recrystallization .…”
Section: Discussionmentioning
confidence: 99%
“…Close analysis revealed that the real pressure applied on the sample was ³4 GPa as discussed later. It should be noted that diamond (111) peaks are visible in the X-ray profiles and this is because the space between the upper and lower anvils was reduced due to the loading so that the X-ray now illuminated on the sample together with the anvils. It should be also noted that the presence of the ¢ phase was not expected for the conditions of pressure and temperature adopted in this study based on the first-principle calculation reported earlier.…”
Section: Transformation Behaviour During Heating Under Ambient Pressumentioning
confidence: 99%